Gender Transformative Methodologies CoP. Masculinities conversation 1 - Engaging men for gender equality - tools from Equimundo - Vess, Joseph; Kimonyo, Augustin; Gallagher, Emily; Bailey, Arwen (2024)
Joseph Vess and Augustin Kimonyo, both fellows of Equimundo and members of the MenEngage Alliance, introduced and discussed a new toolkit for ‘ENGAGING MEN FOR GENDER EQUALITY IN RURAL TRANSFORMATION PROJECTS'. The toolkit is part of a collection developed under an IFAD-funded Women's Resource Rights initiative with CIFOR-ICRAF, the Alliance of Bioversity and CIAT and IFPRI.